A Case Report of Bilateral Phrenic Nerve Dysfunction After Unilateral Supraclavicular Brachial Plexus Block: Unveiling Preexisting Diaphragmatic Dysfunction. Issue 4 (30th March 2021) - Castro, Anne L.; Chen, Christina; Bronshteyn, Yuriy; Ray, Neil; Gadsden, Jeff
Abstract : Supplemental Digital Content is available in the text. Abstract : A 48-year-old woman with a history of cardiac surgery developed severe dyspnea and anxiety following right-sided supraclavicular nerve block for hand surgery. In this case, right phrenic nerve blockade from a supraclavicular block unmasked a subclinical hemidiaphragmatic paresis from phrenic nerve injury on the left, the latter likely due to previous cardiac surgery. When performing brachial plexus block at or above the clavicle, particularly for prior cardiothoracic surgical patients, anesthesiologists can easily, quickly, and inexpensively use point-of-care ultrasound to assess whether any degree of phrenic nerve dysfunction exists on the contralateral side, as patients may be asymptomatic at baseline.